Comparisons of local and systemic aerobic fitness parameters between finswimmers with different athlete grade levels - Wang, B.; Tian, Q.; Zhang, Z.; Gong, H. (European Journal of Applied Physiology, 2012)
To study the relationship between the local and systemic aerobic fitness parameters, and between the muscle oxygenation and aerobic performance, 16 female finswimmers were recruited and divided into high-level (HL) group and low-level group. Cardiorespiratory function, blood lactate concentration and near infrared spectroscopy muscle oxygenation in the vastus lateralis (VL) were monitored simultaneously during a maximal incremental exercise. We found that the break point (Bp) of the oxygenation index (OI) in the VL (BpVL) had significant correlations with lactate threshold (LT) and gas exchange threshold (GET), and the appearance sequence of the three thresholds was BpVL ˜ LT = GET. When considering different levels, the VO2at BpVL, LT and GET were higher in the HL group. During intensive exercise, there were significantly faster VO2increase and evidently slower OI decrease in the HL group, suggesting that faster [(V)\dot]\textO2 VO2increase in the HL group slowed down the muscle deoxygenation and facilitated subjects to cycle to higher workloads. In conclusion, multi-modality approaches combining local and systemic physiological monitoring technologies might provide better explanations of the relationship between local and systemic aerobic fitness parameters, and might be a novel way to analyze the difference between groups of different levels.